Synthesis of silver nanoparticles by green method using ligustrum sinense to study their structural and photoluminescence properties - Khan, Sh; Patel, S.; Shukla, P.; Kumar, R.; Dixit, R. (Eurasian Journal of Physics and Functional Materials, 2026)
Photoelectronic devices such as solar cells require an electrolyte with electrode that has high energy conversion efficiency. Hence, ionic electrolyte and blend polymer composite electrolyte helps in ion regeneration and improving the performance of the device. Introduction of metal nanoparticles in the polymers such as the PMMA, PVDF provides this enhancement of performance. Nanoparticles are manufactured in an eco-friendly manner and characterized by UV and XRD. In this work we present the possibility that could be explored with the incorporation of nanoparticles and also see the synthesis process of green nanoparticles. The excitons dissociation in these devices could increase with the introduction of nanoparticles. They exhibit a near field surface plasmon resonance effect which couples with the existing photoactive layer, increasing the absorption cross section. We propose that these non-toxic and bio-friendly nanoparticles are very beneficial in our quest of green energy.Recommended CitationKhan, Sh.A.; Patel, S.; Shukla, P.; Kumar, R.; and Dixit, R. (2023) "Synthesis of silver nanoparticles by green method using ligustrum sinense to study their structural and photoluminescence properties," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 1, Article 3.DOI: https://doi.org/10.32523/ejpfm.2023070104